Contribution to the taxonomy of Eastern North American Epeorus Eaton (Ephemeroptera: Heptageniidae) - Webb, J. M.; Mccafferty, W. P. (Zootaxa, 2006)
The larva of Epeorus punctatus (McDunnough) is described for the first time based on reared specimens from West Virginia. Larvae are differentiated from those of other E. vitreus species group species by the bluntly pointed femoral projections, subrectangular head capsule, and short posterolateral abdominal projections. Epeorus rubidus (Traver) is considered to be a junior subjective synonym of E. vitreus (Walker). A key for the known larvae of the eastern North American species of the E. vitreus species group [E. dispar (Traver), E. punctatus, E. subpallidus (Traver), E. vitreus] is provided.